Quality of life outcomes in multiple myeloma patients: a summary of recent clinical trials. Issue 8 (3rd August 2019) - Martino, Massimo; Rossi, Marco; Ferreri, Anna; Loteta, Barbara; Morabito, Antonella; Moscato, Tiziana; Console, Giuseppe; Innao, Vanessa; Naso, Virginia; Provenzano, Pasquale Fabio; Recchia, Anna Grazia; Gentile, Massimo
ABSTRACT: Introduction : Management of multiple myeloma (MM) has improved over recent years. Health-related quality of life (HRQoL) data is becoming increasingly important, owing to improved survival outcomes. Areas covered : The authors performed an expert review of the literature to identify evidence-based data available on HRQoL in frontline and relapsed/refractory MM (RRMM) patients. Expert opinion : De-novo patients should be informed that the HRQoL is expected to improve during first-line treatment with different degrees of possible deterioration during the first cycles. Achievement of a maximal response should be strongly considered, particularly in the frontline setting, but must also be balanced with tolerability, HRQoL, and patient preferences. The same degree of improvement in HRQoL cannot be expected during conventional relapse treatments, where patients should be prepared only for stabilization of HRQoL. However, focusing attention only on measures such as toxicity may provide just a partial view of overall treatment effectiveness. Nonetheless, the authors believe the added value of taking into consideration the patient's perspectives and the importance of patient-reported outcomes in the evaluation of treatment effects should be considered mandatory. The incorporation of quality of life assessment into clinical and research practice has the potential of improving treatment outcomes.